Russisches (?) Pärchen zeigt auf der Bühne einen Folklore-Tanz
internationale Politik (allgemein);internationale Beziehungen;Politik der Zusammenarbeit;kulturelle Zusammenarbeit politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Kommunismus soziale Fragen;Kultur und Religion;Kulturpolitik;kulturelle Veranstaltung